Tutulena: A Heritage Folk Game as the Foundation of Malind Cultural Character Formation - Trinovianto George Reinhard Hallatu; Ni Nyoman Rediani; Ivylentine Datu Palittin (Indonesian Values and Character Education Journal, 2025)
Character development has become a major concern due to the high incidence of bullying experienced by children, adolescents, and adults. Efforts to address this issue have been carried out through the implementation of innovative learning models and approaches grounded in local wisdom. This study aims to analyze the values embedded in the traditional folk game Tutulena as a means of character formation. The study employs a qualitative approach with research subjects that include children, adolescents, adults, and parents. Data were collected through documentation, interviews, and literature review, and subsequently analyzed using data triangulation. The findings indicate that Tutulena instills essential values such as cooperation, discipline, patience, perseverance, courage, sportsmanship, and cultural preservation. These values play a significant role in shaping positive character, as individuals learn to respect others, communicate effectively, and collaborate to achieve common goals through interactions in the game. The results confirm that Tutulena is not only recreational but also has the potential to serve as an effective medium for character education. The study’s implications suggest that integrating traditional games into the learning process can strengthen culture-based character education.